2001
DOI: 10.1097/00006565-200104000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Management of febrile infants and children by pediatric emergency medicine and emergency medicine: Comparison with practice guidelines

Abstract: There is poor compliance with published practice guidelines in the management of febrile infants and children among PEM and EM directors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0
8

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 16 publications
1
28
0
8
Order By: Relevance
“…Several studies have been published, however, that examine differences between pediatric and general emergency departments in the management of bronchiolitis and, as well, several other diseases. [47][48][49][50][51][52][53] Although several studies used surveys to assess opinions regarding various management strategies, [47][48][49] some also used a retrospective methodology to establish actual differences in practice patterns between pediatric and general emergency physicians. 50 -53 In general, retrospective studies are thought to provide poorer quality data than that obtained from a prospective study design.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published, however, that examine differences between pediatric and general emergency departments in the management of bronchiolitis and, as well, several other diseases. [47][48][49][50][51][52][53] Although several studies used surveys to assess opinions regarding various management strategies, [47][48][49] some also used a retrospective methodology to establish actual differences in practice patterns between pediatric and general emergency physicians. 50 -53 In general, retrospective studies are thought to provide poorer quality data than that obtained from a prospective study design.…”
Section: Discussionmentioning
confidence: 99%
“…O documento estratifica as crianças por faixa etária e, ainda, pelo risco para IBG (baixo e alto), através de crité-rios clínicos e laboratoriais. A partir dele, várias estratégias foram elaboradas no intuito de padronizar a abordagem das crianças com FSSL 1,2,4,[15][16][17] .…”
Section: Introductionunclassified
“…12 Studies on variation and adherence to existing practice guidelines for evaluation and management of fever in young infants have been limited to surveys or adherence to recommended urine testing or have excluded neonates 0-28 days of age. [13][14][15] Belfer et al 16 conducted a survey-based study on compliance with guidelines for the management of febrile infants and found 54% compliance among pediatric emergency medicine directors. To our knowledge, no large multi-institutional study has reported actual practice for the management of febrile neonates in terms of variation and adherence to standard recommendations in pediatric emergency departments (PEDs) in the United States.…”
mentioning
confidence: 99%